Molecular mechanisms and therapeutic strategies in amyotrophic lateral sclerosis caused by C9orf72 mutations. (25th February 2016) - Balendra, Rubika; Mizielinska, Sarah; Moens, Thomas; Niccoli, Teresa; Ridler, Charlotte; Simone, Roberto; Woodling, Nathan; Parkinson, Gary; Neidle, Stephen; Patani, Rickie; Partridge, Linda; Isaacs, Adrian
Abstract: Background: A hexanucleotide expansion in C9orf72 is a common cause of the fatal neurodegenerative disorder amyotrophic lateral sclerosis. We have found evidence in a Drosophila model that neurotoxicity is mediated by dipeptide repeat (DPR) proteins generated by repeat-associated non-ATG translation. Here we aimed to evaluate in models of amyotrophic lateral sclerosis caused by the C9orf72 mutation ( C9orf72 -ALS) whether DPR proteins cause nucleolar dysfunction and whether novel small molecules that bind C9orf72 -repeat RNA reduce DPR formation and neurotoxicity. Methods: We assessed nucleolar function in in-vivo Drosophila models. Nucleolar size was measured with immunofluorescence and confocal microscopy, using automated image analysis. Human induced pluripotent stem cells (iPSCs) from patients with C9orf72 -ALS and from healthy controls were taken through neural induction and patterning to derive spinal motor neuron populations. Disease phenotypes were measured with fluorescence in-situ hybridisation for the typical RNA foci seen in C9orf72 -ALS patients. Small molecules binding to C9orf72 -repeat RNA were fed to C9orf72 Drosophila and applied to the human iPSC-derived spinal motor neurons to evaluate rescue of disease phenotypes. Findings: DPR proteins colocalised with nucleoli in C9orf72 - Drosophila brain tissue, with effects on nucleolar morphology. C9orf72 - Drosophila had significantly reduced egg-to-adult viability (p<0·05), and the bioavailability of the small molecules in Drosophila was investigated. Interpretation: Emerging evidence suggests that nucleolar dysfunction is a key mechanism in C9orf72 -ALS. It is crucial that this finding is validated in relevant disease models to rapidly translate findings into promising therapeutic targets. The high prevalence of C9orf72 -ALS makes use of targeted therapies a compelling strategy. These experiments might provide novel mechanistic insights into a common form of amyotrophic lateral sclerosis and deliver preclinical data on an exciting therapeutic approach. Funding: RB is a Leonard Wolfson Clinical Research Training Fellow and is funded by a Wellcome Trust Clinical Research Training Fellowship (107196/Z/14/Z).